Strategic aims of Šāpur II during the campaign in northern Mesopotamia (359-360) - MAKSYMIUK, Katarzyna (Historia i Świat, 2018)
In 359, Šāpur II (r. 309-379) led his army against Rome. This campaign became a milestone for the balance of power in Romano-Iranian borderlands. After seventy three Šāpur succeeded in breaking through the defenses and in sacking the city of Amida . According to Ammianus Marcellinus long lasting, heroic defense of Amida saved the Roman cities of Cappadocia from sacking. The author of the article believes that Amida was initial and primary target of Šāpur’s campaign of 359 and the siege was not a result of coincidence of various events, factors and intentions not, as it is suggested by Ammianus Marcellinus